The complete chloroplast genome of Corydalis wilsonii N. E. Brown 1903 and its phylogenetic analysis - Feng Han; Tao Dou; Chuan Luo; Xuhong Song; Pinming Li; Maoxiang Lin (Mitochondrial DNA. Part B. Resources, 2025)
Species within Corydalis are valued for medicinal and ornamental uses but taxonomic uncertainties persist due to limited genomic data. Here, we present the complete chloroplast genome of C. wilsonii, with a quadripartite structure of 191,388 bp and 140 functional genes. Phylogenetic analysis robustly resolves C. wilsonii within a monophyletic clade alongside C. saxicola, C. tomentella, and C. fangshanensis, all nested within sect. Thalictrifoliae (bootstrap support = 100%). This study expands the chloroplast genomic resources for Corydalis and establishes a taxonomic framework to refine species identification and resolve evolutionary relationships within this ecologically and economically vital genus.